Dampak Electronic Word of Mouth dan Percieved Value dalam Meningkatkan Online Repurchase Intention pada Platform Tokopedia - Shendy Amalia; Ratih Hurriyati; Puspo Dewi Dirgantari (Coopetition : Jurnal Ilmiah Manajemen, 2023)
With the growth of e-commerce in Indonesia which continues to increase every year, it creates business opportunities, especially in the e-commerce. As a platform with the number one user in Indonesia, Tokopedia, focuses on its sustainability in terms of online repurchase intention. This study aims to describe and measure how much influence Ewom has, perceived value, in increasing online repurchase intention both partially and simultaneously among Tokopedia application users. This type of research is descriptive verification and explanatory survey with random sampling technique, with a total sample of 210 respondents using the Tokopedia application. The analysis technique used is the Structural Equation Model (SEM) method with the Smart PLS 3.0 tool. The results show that the description of each variable is in the high category. There is influence both simultaneously and partially. With a magnitude of influence of 63.9%. For the partial effect of the Ewom it has no effect on Online Repurchase Intention. While the variable Perceived Value partially has a significant influence on Online Repurchase Intention.